2010
DOI: 10.1111/j.1365-2966.2010.16923.x
|View full text |Cite
|
Sign up to set email alerts
|

A kinematic study of the neutral and ionized gas in the irregular dwarf galaxies IC 4662 and NGC 5408★

Abstract: The feedback between massive stars and the interstellar medium is one of the most important processes in the evolution of dwarf galaxies. This interaction results in numerous neutral and ionized gas structures that have been found both in the disc and in the halo of these galaxies. However, their origin and fate are still poorly understood. We here present new H i and optical data of two Magellanic irregular dwarf galaxies in the Local Volume: IC 4662 and NGC 5408. The H i line data were obtained with the Aust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 51 publications
3
26
0
Order By: Relevance
“…Following these models, the expansion velocity of the outflows will never get close to or beyond the escape velocity due to the presence of a dark matter halo (in our case, maybe the huge amount of neutral gas that is surrounding the main body of the galaxy is also playing an important role) that slows down the gas expelled by the galactic winds. In fact, the expansion velocities of the gas computed by van Eymeren et al (2010) are 30–50 per cent the escape velocities.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Following these models, the expansion velocity of the outflows will never get close to or beyond the escape velocity due to the presence of a dark matter halo (in our case, maybe the huge amount of neutral gas that is surrounding the main body of the galaxy is also playing an important role) that slows down the gas expelled by the galactic winds. In fact, the expansion velocities of the gas computed by van Eymeren et al (2010) are 30–50 per cent the escape velocities.…”
Section: Discussionmentioning
confidence: 94%
“…We now compare the features of the neutral gas component found in NGC 5253 with the other starbursts described in the literature. Recent analyses of the neutral gas component of dwarf starburst galaxies include NGC 2366 (van Eymeren et al 2009a), NGC 4861 (van Eymeren et al 2009b), NGC 5408 and IC 4662 (van Eymeren et al 2010). All these galaxies have the common characteristic of showing outflows of neutral gas that follows the ionized gas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This weakening of the central dark matter cusp occurs even if there is no escape of baryonic matter from the galaxy. On the observational front, van Eymeren et al () as well as Cannon et al () both find evidence for feedback from star formation into the neutral ISM of dwarf galaxies. But even though our galaxies represent some of the smallest mass, actively star‐forming systems, feedback between the star formation on the neutral gas distribution in two of them (d0958+66 and d1028+70) is not clearly evident.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the Hα kinematics have shown that galactic winds are common in BCDs, but the velocities of the Hα gas are usually smaller than the escape velocities (Martin 1996(Martin , 1998van Eymeren et al 2009bvan Eymeren et al ,a, 2010, implying that the ionized gas is gravitationally bound to the galaxy. Similar results have been found by studies of the Na D absorption doublet (Schwartz & Martin 2004).…”
Section: Stellar Feedback and Gas Outflowsmentioning
confidence: 99%